Employability skills for an entry-level engineer as seen by Malaysian employers - Yuzainee M.Y.; Zaharim A.; Omar M.Z. (2023)
In an earlier publication, the authors have proposed a model on practical framework of engineering employability skills, i.e. the Malaysian Engineering Employability Skills (MEES). The framework discusses on the possible employability skills as required for an entry level engineer in Malaysia based on many other earlier studies. A set of questionnaires was later developed to gauge this model from the perspective of Malaysian employers from engineering sectors. Based on the results obtained, this paper will discuss, among others, the preferred entry-level employability skills as valued by employers when hiring fresh engineering graduates. The data was collected from September to December 2009 through face-to-face and telephone interviews with employers from Kelang Valley area, the main industrial area in Malaysia. Five hundreds employers were approached, and of this, three hundreds were successfully interviewed. The interviews were only carried out with high ranking officers, in this case; Head of Division or higher to assure accurate results. The questionnaires comprise ten (10) main employability skills as described in MEES. A "multi-attribute value technique" and statistical methods were used for data analysis. The findings suggested that the employers perceived employability skills as "required" with an average rating score of 4.06 out of 5.00. The most required skill is "communication skills" while the least required is "engineering system approach". However, there are differences in the priorities of employability skills by the four different categories of industries considered in this study. The framework and the findings presented perhaps can be used as guidance for the employers in their recruitment exercise. The findings could also be helpful in guiding the education providers, trainers, career advisors and the likes in increasing the employability skills of engineering fresh graduates. 2011 IEEE.